TEACHING SCHOOL IN THE 1890s - Talley, William M. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1991)
These letters of a young teacher,lohn Fowler, give a picture of teaching in a one-room school in the 1890s. The letters tell of his relations with parents, pupils, trustees, and people in the community and describe the living arrangements of a teacher in a remote region of the United States. RÉSUMÉ Ces lettres d'un jeune professeur, John Fowler, brossent un tableau de l'enseignement dans une école à une seule salle dans les années 1890. Ces lettres relatent les relations entre ce jeune professeur, ses parents, ses élèves, les membres du conseil d'administration et de la communauté et décrivent les conditions de vie d'un professeur vivant dans une région reculée des États Unis.